Monoaminergic neurotransmission is altered in hepatitis C virus infected patients with chronic fatigue and cognitive impairment - Weissenborn, K (BMJ Group, 2006)
BACKGROUND: The majority of patients with hepatitis C virus (HCV) infection suffer from disabling fatigue, cognitive dysfunction, and quality of life reduction. Meanwhile, there is increasing evidence that HCV infection can affect brain function. Recent studies have shown that fatigue and psychomotor slowing may resolve in patients with hepatitis C after treatment with ondansetron. This observation indicates alteration of serotonergic neurotransmission in HCV infected patients with chronic fatigue. METHODS: Data from 20 HCV infected patients who were referred to our clinic because of disabling fatigue and cognitive decline of unknown cause were analysed retrospectively. Patients had undergone a diagnostic programme, including clinical and psychometric examination, electroencephalogram (EEG), magnetic resonance imaging of the brain, cerebrospinal fluid analysis, and I‐123‐beta‐CIT (2β‐carbomethoxy‐3‐β‐(4‐[(123)I]iodophenyl)tropane) single photon emission computerised tomography (SPECT) studies of serotonin and dopamine transporter binding capacity. RESULTS: All patients had pathological results on the fatigue impact scale. Two thirds of patients showed pathological attention test results. EEG, magnetic resonance imaging, and cerebrospinal fluid analysis were normal. Pathological dopamine transporter binding was present in 12/20 (60%) patients and pathological serotonin transporter binding in 8/19 (50%) patients. Patients with normal SPECT results did not significantly differ from controls with regard to psychometric test results. Interestingly, patients with both decreased serotonin and dopamine transporter binding showed significantly impaired performance in most of the tests applied. Comorbidity that could have impaired cerebral function was excluded in all patients. CONCLUSION: Our findings indicate alteration of serotonergic and dopaminergic neurotransmission in HCV infected patients with chronic fatigue and cognitive impairment.